Understanding farmer cooperatives’ intention to adopt digital technology: mediating effect of perceived ease of use and moderating effects of internet usage and training - Andi Cao; Lili Guo; Houjian Li (International Journal of Agricultural Sustainability)
Digital transformation is an inevitable trend, and adopting digital technology in farmer cooperatives boosts production and efficiency. This study combines the Technology Acceptance Model and the Technology-Organization-Environment framework to explore farmer cooperatives’ intention to adopt digital technology. Using data from 230 Chinese cooperatives engaged in cultivation, we identify key factors and mechanisms influencing their adoption intention, applying partial least squares method. The results indicate that both perceived ease of use and perceived usefulness have significant positive effects on the intention to adopt digital technology. Perceived ease of use also enhances perceived usefulness. In addition, government support and competitive advantage contribute to improving cooperatives’ perceptions of both the ease of use and usefulness of digital technology. Organizational competency is found to play a crucial role in facilitating the perceived ease of use of digital technology. Moreover, the cooperative chairman's internet usage and participation in vocational training strengthen the positive relationship between perceived ease of use and digital technology adoption intention. Government support and organizational competency also indirectly enhance the intention to adopt digital technology by improving cooperatives’ perceived ease of use. This study provides key insights for developing government policies to promote the digital transformation of farmer cooperatives.